THE INFLUENCE OF SOCIAL AND ECONOMIC ASPECTS ON FISH CONSUMPTION TRENDS AMONG GENERATION Z INKENDARI CITY: PENGARUH ASPEK SOSIAL EKONOMI TERHADAP TRENKONSUMSI IKAN PADA GENERASI Z DI KOTA KENDARI - Baihaqi; Ika Rezvani Aprita; Sri Agustina; Windayani; Harmiaty Bahar; Fatahu; Andi Laila Nugrawati M (ROCE : Jurnal Pertanian Terapan, 2025)
This study aims to analyze fish consumption trends among Generation Z in Kendari, focusing on the social and economic factors that influence these trends. Generation Z, born between 1997 and 2012, shows diverse consumption preferences. Factors affecting fish consumption patterns in this group include frequency, motivation, preference for fish types, knowledge of fish benefits, as well as social, cultural, and economic influences such as fish prices. The study found that most respondents consume fish at least once a week, with a preference for marine fish over freshwater fish. Health benefits are the primary motivation for fish consumption, although knowledge about the health benefits of fish remains limited. The influence of family, peers, and social media plays a dominant role in shaping fish-eating habits. Additionally, the price of fish is a significant barrier in consumption decisionsamong Gen Z. These findings are expected to contribute to policies aimed at increasing the consumption of nutritious fish among the younger generation.